Methanol poisoning outbreak in Saudi Arabia: a case series - Rawan Eskandrani; Khalid Almulhim; Abdulla Altamimi; Abeer Alhaj; Shahd Alnasser; Laale Alawi; Eman Aldweikh; Khalid Alaufi; Bandr Mzahim (Journal of Medical Case Reports, 2022)
Abstract Background Outbreaks of methanol poisoning have been described in the medical literature in different regions around the world. Even though in Saudi Arabia a few outbreaks of methanol poisoning have occurred, they remain undocumented. Herein, we describe several cases of methanol poisoning in Saudi Arabia with the goal of increasing awareness about the dangers of methanol poisoning among healthcare staff. Case presentation Nine middle-aged Saudi patients (five men aged 24, 26, 27, 36, and 49 years and four females aged 19, 20, 24, and 25 years) were admitted to our emergency department after alcohol consumption. All patients presented with severe metabolic acidosis and some visual impairment. Treatment was initiated based on the clinical suspicion of methanol intoxication because of laboratory test limitations and time constraints. Patients showed improvement and favorable hospital outcomes after aggressive empirical treatment. Conclusions Many social and cultural factors influence the lack of reporting of methanol poisoning cases in Saudi Arabia. We believe it is important to document these outbreaks to increase the knowledge among healthcare providers and promote public health awareness. A high index of suspicion and the development of local public health networks to monitor, survey, follow-up, and facilitate data exchange can help healthcare providers recognize and aggressively treat affected individuals. Early empiric and aggressive management can greatly decrease morbidity and mortality despite challenges and limited resources.